Transgelin-2 is upregulated on activated B-cells and expressed in hyperplastic follicles in lupus erythematosus patients. - Kaori Kiso; Hajime Yoshifuji; Takuma Oku; Masaki Hikida; Koji Kitagori; Yoshitaka Hirayama; Toshiki Nakajima; Hironori Haga; Tatsuaki Tsuruyama; Aya Miyagawa-Hayashino (PLoS ONE, 2017)
Transgelin-2 (TAGLN2) is an actin-binding protein that controls actin stability and promotes T cell activation. TAGLN2 is also expressed on B-cells but its function in B-cells is unknown. We found that TAGLN2-expressing B-cells were localized in the germinal center (GC) of secondary lymphoid tissues and TAGLN2 mRNA was significantly upregulated after IgM+IgG stimulation in primary human B-cells, suggesting that TAGLN2 was upregulated upon B-cell activation. In support of this, lymph nodes (LNs) from patients with systemic lupus erythematosus (SLE), in which the intense GC activity have been recognized, showed increased TAGLN2 expression in B-cells compared to control LNs. Moreover, TAGLN2+B-cells were distributed widely not only in the GC but also in the perifollicular areas in SLE LNs. In contrast, CD19+ B-cells and CD19+CD27+ memory-B cells in peripheral blood of SLE patients showed no increase in TAGLN2 mRNA. Two-photon excitation microscopy of Raji cells demonstrated that TAGLN2 colocalized with F-actin and moved together to the periphery upon stimulation. TAGLN2-knockdown in Raji cells resulted in impaired phosphorylation of PLCγ2 leading to inhibition of cell migration. Microarray analysis of TAGLN2-knockdown Raji cells showed decreased expression of the genes associated with immune function including CCR6 and as well as of those associated with regulation of the actin cytoskeleton including ABI2, compared to controls. These results suggest that TAGLN2 might regulate activation and migration of B-cells, in particular, the entry of activated B-cells into the follicle. We also suggest that TAGLN2 could be used as a marker for activated B-cells.